The European Portuguese Version of the Determinants of Meditation Practice Inventory-Revised (DMPI-R) - Monteiro, Bárbara (2022)
Meditation practice has beneficial effects on physical and mental health, and barriers to regular practice have been recognized. The Determinants of Meditation Practice Inventory (DMPI) was developed and recently revised (DMPI-R). DMPI-R is a 12-item self-report instrument encompassing four dimensions: low perceived benefit, perceived inadequate knowledge, perceived pragmatic barriers, and perceived socio-cultural conflict. The current study aimed to investigate the psychometric properties and factor structure of the European Portuguese version of the DMPI-R in a general population Portuguese sample (non-meditators).